TRANSLATION STRATEGIES FOR CULTURAL EXPRESSIONS IN GARUDA INDONESIA’S INFLIGHT MAGAZINE "COLORS" - Rizky Salsabila; Jumanto Jumanto (BASIS (Bahasa dan Sastra Inggris), 2020)
The aims of this research were to find the translation strategies, translation accuracy, and translation readability of cultural expressions in tourism texts of the Garuda Indonesia Inflight Magazine Colors. The research used a descriptive – qualitative method. To achieve the aims of this study, the researcher used some techniques to analyze the data such as reading and collecting data, encoding data, underlining the cultural expressions in the tourism texts, assessing translation accuracy, assessing translation readability, categorizing types of translation strategies and drawing conclusion. Based on the data analysis from three expert judgements, it was found that 84.5% of the data were accurate because the expressions in the target language have equivalent meaning with the source language; 15.5% of the data were less accurate because the expressions had no equal meaning with the source language and the equivalence seemed less natural; and 0% of the data were inaccurate. Meanwhile, 74% of the data were readable because the translation was very easy to understand; 16.67% of the data were less readable because the translation was not very easy to understand; and 9.33% of the data were unreadable because the translation was difficult to understand. The dominant strategy was the synonymy which got the percentage of 29%, which meant that translators also used the target language words which were more or less the same as the general source language words.